KONSTRUKSI PEMIKIRAN FIKIH SOSIAL KH. SAHAL MAHFUDZ - Muhammad Riyadi; Mukhsin Achmad (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This article reviews Islamic law and fiqh as a side of Islam that many struggle with the dynamics of life. Fiqh which is related to the reality of everyday life is a treasure that is wide open across time, time and human development itself. In reality, the idea of ​​fiqh is mostly positioned as an absolute and tsawabit science, so that it becomes difficult to develop a spirit of ijtihad and reformation in a syumuli manner. This is where K.H Sahal Mahfudz tries to position fiqh as an analysis that is able to answer society's problems in a more progressive and transformative way. Social, societal and cultural conditions are facts of the ummah that also need a sharia foundation. This alignment and dialectic of fiqh with the social life of society is what K.H Sahal Mahfudz raised as a form of revitalization of sharia teachings that is sensitive to the ummah. It is hoped that the concept of social fiqh offered by KH Sahal Mahfud will actualize and optimize fiqh as a system of values ​​and behavior that continues to develop in society.